"Girls were seen crying when soldiers departed." Belgian and French women and German soldiers: transgressive relationships under the gaze of the occupied population. Issue 2 (4th May 2018) - Debruyne, Emmanuel
ABSTRACT: Between 1914 and 1918, the German army occupied Belgium and large parts of France. One important feature of the occupation was the gender imbalance and, as such, these French and Belgian territories were often the theatre of encounters between the occupation soldiers and local women. Intimate relationships among them were not uncommon: one can find comments about them in two thirds of the diaries kept by people living under the German occupation. This article is based on the analysis of a corpus of 110 such diaries,   revealing the way people perceived and judged these relations, but also the variations in this perception, geographical, chronological, social or gendered. Some of these diaries – especially when written by young women – also provide clues about different aspects (like harassment or occupation languor) of the 'psychological soil' in which these relations could emerge. In occupied France and Belgium most people considered these relationships to be appalling from a patriotic and moral point of view, and their sheer number was viewed as a concern, but some diarists tried to understand the origins of the phenomenon. The different interpretations suggested explanations such as gender, class, age, education, the length of the conflict or misery, but rarely demonstrated empathy for those who were called 'femmes à Boches' ('women for the Huns'). Prostitution flourished from the start of the occupation and was completely at odds with the standards emanating from the "occupied war culture". This rise provoked an outcry and disgust among the population: its expansion and its association with the occupier inflamed its visibility in public space, making it partly inhospitable to the occupied people. Weddings, in contrast, were extremely rare, and only reported in a few diaries. This quasi absence of formalized relations did not prevent the birth of numerous children born to a French or Belgian woman and a German soldier. These babies were generally officially recorded as having an 'unknown father' and were not welcome in the community, despite the anxieties generated by a drop in the birth rate during the occupation period. With the rise in sexual encounters between occupation soldiers and local women, venereal diseases became a common concern to both the occupiers and those occupied. During the first winter of the occupation, measures were taken by the German and local authorities to try to stop the spread of sexually transmitted diseases. Centers specialized in the (forced) treatment of women infected by venereal disease were created by the occupying authorities. These centers were sometimes nicknamed ' parc à poules ' ('chicken parks') by the occupied population, ashamed of their very existence, but eager to see the 'purification' of the public space through the arrest of prostitutes and infected women. All in all, the various forms of intimate relationships were more often reported in the Operations - und Etappengebiet, close to the front, than on the territory of the general-government, where the density of the German presence was lower. But everywhere, these relationships – generally regarded as venal sexuality – aroused animosity and led to these women being ostracised.